Analisis Komprehensif Tentang Konsekuensi dan Upaya Penanggulangan Penangkapan Ikan yang Melanggar Hukum - Tampubolon, Vernandito Sudharta Raftua; Triadi, Irwan (Media Hukum Indonesia (MHI), 2024)
Indonesia has great potential from marine resources that have not been managed to the fullest and require complete and accurate data for optimal utilisation. These resources can support national economic progress, but illegal practices such as fishing hinder this potential. Illegal fishing causes huge losses to the state, local fishermen, and consumers. Overlapping regulations and lack of institutional clarity complicate addressing this issue. Although legal reform efforts have been made, national and international co-operation is needed to address these challenges for the sustainability of marine resources and the welfare of coastal communities. This research uses a normative legal research method, which relies on the analysis of library materials, secondary data, legal principles, legal principles, and legal doctrines to resolve the legal issues formulated. Sustainable law enforcement is expected to provide a deterrent effect for foreign fishermen. The issue of illegal fishing is not only about the loss of fisheries resources, but also about the violation of state sovereignty which is very principled. Therefore, law enforcement and sovereignty must be strictly enforced.